Turning the Lights on Across Africa - World Bank (Washington, DC, 2014)
Africa is in the midst of a power crisis. Despite abundant low-carbon, a low-cost energy resource, Africa faces chronic energy shortages. The region s power generation capacity is lower than that of any other region in the world, and when compared with other developing regions, its capacity growth has stagnated. The power crisis is the result of several constraints that, together, create a vicious cycle. Africa's electricity access is the worst in the world. Almost 70 percent of the continent s population (nearly 600 million people) and 10 million small- and medium-sized enterprises have no access to electricity. Sub-Saharan African's(SSA) account for nearly 45 percent of people lacking electricity across the globe. Most regions in the world have urban electrification rates of 90 percent or higher; in SSA, less than 60 percent of those living in urban areas have electricity. If current electricity connection trends continue, fewer than 40 percent of SSA countries will reach universal access to electricity by 2050.